TAS-116 inhibits oncogenic KIT signalling on the Golgi in both imatinib-naïve and imatinib-resistant gastrointestinal stromal tumours - Saito, Yurina (Br J Cancer, 2019)
BACKGROUND: Despite the effectiveness of imatinib mesylate (IM), most gastrointestinal stromal tumours (GISTs) develop IM resistance, mainly due to the additional kinase-domain mutations accompanied by concomitant reactivation of KIT tyrosine kinase. Heat-shock protein 90 (HSP90) is one of the chaperone molecules required for appropriate folding of proteins such as KIT. METHODS: We used a novel HSP90 inhibitor, TAS-116, which showed specific binding to HSP90α/β with low toxicity in animal models. The efficacy and mechanism of TAS-116 against IM-resistant GIST were evaluated by using IM-naïve and IM-resistant GIST cell lines. We also evaluated the effects of TAS-116 on the other HSP90 client protein, EGFR, by using lung cell lines. RESULTS: TAS-116 inhibited growth and induced apoptosis in both IM-naïve and IM-resistant GIST cell lines with KIT activation. We found KIT was activated mainly in intracellular compartments, such as trans-Golgi cisternae, and TAS-116 reduced autophosphorylated KIT in the Golgi apparatus. In IM-resistant GISTs in xenograft mouse models, TAS-116 caused tumour growth inhibition. We found that TAS-116 decreased phosphorylated EGFR levels and inhibited the growth of EGFR-mutated lung cancer cell lines. CONCLUSION: TAS-116 may be a novel promising drug to overcome tyrosine kinase inhibitor-resistance in both GIST and EGFR-mutated lung cancer.